Adherence to the Mediterranean diet of pregnant women in Central South Africa: the NuEMI study - Spies, Hermina Catharina; Nel, Mariette; Walsh, Corinna May (SAGE, 2022)
Introduction: The Mediterranean diet (MeD) has been shown to have significant health benefits for adults and children. A mother’s diet during pregnancy directly impacts the health of her offspring. This study aimed to investigate the adherence to the MeD of pregnant women attending antenatal care at a Regional Hospital in Bloemfontein, South Africa (SA). Methods: A cross-sectional study was conducted on a consecutive sample of 681 pregnant women who attended the antenatal clinic of a Regional Hospital in Bloemfontein. Socio-demographics included: age, highest level of education, household income, employment status, and income stability. Food group intake was assessed with a quantitative food frequency questionnaire. The adapted Mediterranean Diet Adherence Screener (MeDAS) consisted of 13 of the original 14 questions that measured intake of key food groups (score of ⩽7 poor, 8-9 moderate, ⩾10 good) (wine intake was excluded for pregnant women). Results: A total of 681 pregnant women with a median age of 31.8 years (IQR: 26.8-36.5 years) and a median gestational age of 32.0 weeks at the time of the interview participated in the study. The vast majority showed poor adherence to the MeD (99.6%), with only 0.4% (n = 3) having moderate adherence and 0% good adherence. The median adherence score was 5 points and the maximum 8 points. Of those with poor adherence, only 11.5% had tertiary education, 43.2% earned less than R 3000 (<201 USD) per month, 52.5% were unemployed, and 42.0% did not have a stable income in the past 6 months. Of the 3 participants with moderate adherence, all had grade 11 to 12 education, 2 out of the 3 earned more than R3000 (201 USD), one was unemployed, and 2 had a stable income over the past 6 months. Compared to those with an income ⩽ R3000 (⩽201 USD), those with an income above R3000 were significantly more likely to eat nuts (including peanuts) (2.0% vs 4.6%, P = .05), and adhere to sofrito (similar to tomato and onion relish) intake (9.2% vs 15.6%, P = .02). Compared to those who only had a primary education level up to grade 10 (n = 229), those who had a secondary education level or more (grade 11 and higher, n = 452) were significantly more likely to consume enough olive oil per day (1.3% vs 5.0%, P = .01), and to consume sofrito (6.6% vs 18.0%, P = .02). Conclusion: Pregnant participants showed poor adherence to the MeD. Although almost all women fell in the poor adherence group, secondary education contributed to consuming recommended amounts of olive oil and sofrito and higher income was associated with an adequate intake of nuts and sofrito. Based on the findings, we recommend the development of a contextualized MeDAS tool that includes foods that are typically eaten by most South Africans for similar MeD benefits.
Keywords: Mediterranean diet adherence; Pregnant